Investigation On Experimental Surface Chloride Concentration In Concrete - Nuralinah, Devi (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2013)
Surface chloride of concrete as boundary condition is investigated based on the exposure test results obtained by the wind tunnel. Specimens are continuously exposed to controlled airborne salt in the wind tunnel. Several types of boundary condition model are examined based on the obtained experimental results. The dependency of surface chloride on airborne salt and water cement ratio is investigated. Laboratory test on chloride ingress into concrete subjected to airborne salt is carried out by means of the original wind tunnel. The result shows that surface chloride is dependent of intensity of airborne salt. The dependency of surface chloride content on water cement ratio is not clear. Mean surface chloride determined from short-term exposure test underestimates long-term chloride ingress into concrete.Â